Analisis Kompetensi Guru Dalam Penerapan Kurikulum Merdeka Melalui Workshop Di SMP Negeri 2 Gunungsitoli Barat - Elvin Yanti Zebua; Syah Abadi Mendrofa; Robin Markus Putra Waruwu; Sukaaro Waruwu, (Jurnal Ilmu Sosial Dan Politik, 2025)
At SMP Negeri 2 Gunungsitoli Barat, the researcher found a phenomenon of difficulties in understanding and translating the concept of the Independent Curriculum into classroom learning practices. The purpose of this study is to determine the extent of teachers’ competence in implementing the Independent Curriculum, as well as the supporting and inhibiting factors in its implementation after attending workshops at SMP Negeri 2 Gunungsitoli Barat. This research employs a qualitative method with data collection techniques including observation, documentation, and interviews.The results of this study indicate that the implementation of the Independent Curriculum in schools after the workshops still requires adjustments to school conditions, particularly in the use of learning media and teaching strategies that match student characteristics, as well as the availability of budget and training facilities. The inhibiting factors include limited learning facilities and infrastructure, students’ less supportive economic conditions, limited mastery of information technology by some teachers, and the additional workload experienced in preparing learning materials.